Morphological and Syntactical Analysis on Advertising Billboards Used by Hotels in Banjarmasin - Shintya Bella Effendi; Nasrullah Nasrullah; Elsa Rosalina; Fatchul Mu’in (JETAL: Journal of English Teaching & Applied Linguistic, 2023)
It is important to have knowledge of the language to make no mistakes occur in the language. Although previous studies have discussed linguistics and advertising, it is still very rare, and almost very few have discussed the morphology and syntax of hotel billboards in detail. Therefore, to fill this void, this study aimed to examine the morphological and syntactical analysis of advertising billboards used by hotels in Banjar masin. This study used descriptive qualitative research as its methodology. The billboards from various hotels in Banjarmasin served as the study's objects and location. The researcher specifically selected the images from the billboard advertisements that were captured. Then, the data were gathered through making observations and documentation. The findings discovered in the morphology section that numerous hotel advertisements had issues adding suffixes, which were lack of suffix-ly, suffix-s/es for verbs, and suffix-s/es for nouns. Furthermore, the phrase or sentence from the existing hotel billboard has a structural flaw in the syntactic part which is difficult to distinguish with morphology elements. . This study is intended to assist lecturers in the teaching-learning process in terms of morphology and syntax. It is expected that this study would be useful to future researchers conducting pertinent literature.